Womenpreneur On Economic Development in the Digital Economy Era - Desy Arum Sunarta; Alamsyah (Universitas Islam Lamongan, 2023)
The role of women in the economic field can be the main actor and this makes it one of the potential things in micro business activities. Developments in the digital era during the pandemic have encouraged Womenpreneurs to be able to develop their businesses and businesses by conducting online marketing.The digital economy is believed to be able to answer the challenges of developing economic development which until now has not been stable. This digital economy comes with many opportunities to answer existing problems. Based on the results of empirical studies, it was found that there are factors that encourage women to become womenpreneurs, namely: economic factors and independence factors.As the level of participation of womenpreneurs in the digital economy era progresses, there are also challenges, namely the gap in mastery of technology. Another form of problem is creativity and readiness to face digital change. Therefore, more womenpreneurs must be involved so that an increase in participation in digital economy education is needed